2017
DOI: 10.1128/genomea.00317-17
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Dolosigranulum pigrum from a Patient with Interstitial Lung Disease Using Single-Molecule Real-Time Sequencing Technology

Abstract: The whole genome sequence of Dolosigranulum pigrum isolated from the blood of a patient with interstitial lung disease was sequenced with the Pacific Biosciences RS II platform. The genome size is 2.1 Mb with 2,127 annotated coding sequences; it contained two clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated proteins (Cas) systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Nasopharygneal Laclaire et al [10] ? Nasopharyngeal Mukhopadhyay et al [11] 82, M ILD ILD -Lin et al [12] 76, M Cholecystitis --Lecuyer et al [13] 73 [19]. It seems likely that in the case of our patient, he contracted D. Pigrum bacteremia from previously licking his needles.…”
Section: Coinfecting Pathogenmentioning
confidence: 76%
See 1 more Smart Citation
“…Nasopharygneal Laclaire et al [10] ? Nasopharyngeal Mukhopadhyay et al [11] 82, M ILD ILD -Lin et al [12] 76, M Cholecystitis --Lecuyer et al [13] 73 [19]. It seems likely that in the case of our patient, he contracted D. Pigrum bacteremia from previously licking his needles.…”
Section: Coinfecting Pathogenmentioning
confidence: 76%
“…The preponderance of case reports documenting pathology have involved focal eye diseases such as conjunctivitis, keratitis and corneal abscess [1,[6][7][8][9][10]. The pathological spectrum extends to other critical illnesses: synovitis, sinusitis, pneumonia, cholecystitis and septicemia, however it has only rarely been associated with pre-existing immunocompromised states per se (Cystic fibrosis, HIV, Rheumatoid arthritis, Interstitial lung disease, chronic disease, extremes of age) [5,[11][12][13][14][15][16]. Here, we present the case of D. Pigrum bacteremia in an injecting drug user (IDU), in constellation with immunocompromise from comorbid chronic HCV, fungal endophthalmitis and MRSA endocarditis.…”
Section: Introductionmentioning
confidence: 99%
“…Our metagenomic data identified that D. pigrum was the only species that remained group-discriminating after adjustment for HRV status. This bacterium was first described as a new lineage of lactic acid bacterium ( Aguirre et al, 1993 ), and its whole-genome sequence was announced in 2017 ( Mukhopadhyay et al, 2017 ). Recent studies revealed an inverse correlation in RAs between D. pigrum and Staphylococcus aureus , a pathobiont in the respiratory tract ( Liu et al, 2015 ; Escapa et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%